RELATIONAL MARKETING ANALYSIS OF CUSTOMER LOYALTY OF “RUMAH ADAT BUGIS” IN SIDENRENG RAPPANG REGENCY - Hasanuddin, Muhlis; Ramlan, Pratiwi; L, Syahrir (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to analyze the influence of relational marketing on customer loyalty for the "Rumah Adat Bugis" (Bugis Traditional Houses) in Sidenreng Rappang Regency. Relational marketing, which includes key elements such as communication, trust, empathy, and emotional bonding, plays a crucial role in building long-term relationships with customers. By fostering effective communication, trust through consistent service, and understanding customer needs, relational marketing significantly impacts customer loyalty. Loyal customers tend to make repeat purchases, buy in larger quantities, visit more frequently, and recommend the product to others. This research uses a quantitative approach with survey methods, distributing questionnaires to 37 respondents who are customers of the "Rumah Adat Bugis" from 2021 to 2023. Data were analyzed using SPSS software to evaluate the relationship between relational marketing and customer loyalty. The results show that relational marketing positively and significantly influences customer loyalty. This implies that implementing relational marketing strategies effectively strengthens customer retention, increases repeat purchases, and enhances business growth in the traditional housing industry.